Incorporation of hydrophobic silica in a polyvinylidene fluoride membrane: membrane development and performance modeling - Sze Yin, Grace Gan; Nur Fatin Aqilah, .; Normi Izati, Mat Nawi; Shafiq, Mohd Hizam; Nik Abdul Hadi, Md Nordin; Muhammad Roil, Bilad; Zulfan, Adi Putra; Juhana, Jaafar; Norhaniza, Yusof; Nurfaizey, Abdul Hamid; Nadzirah, Mohd Mokhtar (Wiley-VCH Verlag, 2023)
Membrane distillation (MD) performance in seawater desalination can be improved by enhancing the material properties (hydrophobicity, porosity) and process parameters (feed flow rate, temperature). In this study, the effects of hydrophobic silica loading on the properties and MD performance of a polyvinylidene difluoride‐based membrane in seawater desalination were investigated, and a sensitivity analysis (temperature gradient, feed flow rate, salinity) was performed. Incorporation of hydrophobic silica improved the hydrophobicity of the membrane. Higher filler loading increased the number of surface pores while maintaining their size. This resulted in improved flux compared with the neat membrane while maintaining high salt rejection. The optimized membrane was 73 % more efficient than the neat membrane.